A Study of Myths, Facts and Figures on Prominence of Indian Vegetarianism: Past, Present and Future - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana; Devi, Takhelchangbam Brajeshwari; Dolpriya Devi Manoharmayum (Integrated Journal for Research in Arts and Humanities, 2022)
Plants were the primary source of food for early humans. Hinduism and Jainism have consistently urged their devotees to continue with a vegan lifestyle. Supporters of the Orphic secrets were the principal individuals to expound on veggie-lover food in the 6th century BC. Pythagoras, a Greek rationalist, is believed to be the organizer behind moral vegetarianism. Several famous people followed the Pythagorean way of life, which affected vegetarian diets until the 19th century. During the Middle Ages, vegan food essentially quit being eaten in India. Various individuals decided to be veggie lovers during the Renaissance and the Age of Enlightenment. In 1847, India was where the primary vegan culture was framed. In 1908, the International Vegetarian Society was begun, and in 1944, the leading veggie lover society was shaped. Sylvester Graham, John Harvey Kellogg, and Maximilian Bircher-Benner were all notable vegans during this time. Toward the beginning of the 21st hundred years, something changed. Scientists have disproved the old belief that vegetarianism leads to poor nutrition. Instead, they have shown that a vegetarian diet lowers the risk of most modern diseases. Today, vegetarian diets are becoming more popular and accepted all over the world.